2013
DOI: 10.1007/s40141-013-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine in Treating Individuals with Traumatic Brain Injury

Abstract: This article presents an overview of the clinical trials literature on complementary and alternative medicine for traumatic brain injury. In searches of PubMed and the Allied and Complementary Medicine Database, trials of acupuncture, acupressure, creatine, homeopathy, hyperbaric oxygen therapy, mindfulness-based practices, music therapy, neurotherapy, Tai Chi, and yoga were identified. Because of the high risk of bias in most of the studies reviewed, the evidence base is inadequate to recommend any specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Additionally, yoga appears to be beneficial to individuals with TBI by impacting physical, emotional, and cognitive domains. Because cognitive and psychosocial deficits persist or appear as secondary problems later in the TBI disease process, yoga may be a valuable option for individuals in the chronic stage of TBI recovery [3,4,15]. Finally, the results of this study coincide with recent literature acknowledging the functional benefits gained through the use of complementary integrative health approaches in rehabilitation for individuals with TBI [31].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, yoga appears to be beneficial to individuals with TBI by impacting physical, emotional, and cognitive domains. Because cognitive and psychosocial deficits persist or appear as secondary problems later in the TBI disease process, yoga may be a valuable option for individuals in the chronic stage of TBI recovery [3,4,15]. Finally, the results of this study coincide with recent literature acknowledging the functional benefits gained through the use of complementary integrative health approaches in rehabilitation for individuals with TBI [31].…”
Section: Discussionsupporting
confidence: 73%
“…Researchers have found that individuals with chronic conditions who practice yoga may experience improved cognitive functioning, self-awareness, balance, coordination, adjustment to disability, and reduced stress [10,11,13,14]. Because of these benefits, yoga has been suggested as a modality to address many deficits faced by individuals with chronic TBI [15].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that using NSAIDs and opioids exerts a wide range of adverse effects ( 14 , 15 ), there is currently a strong interest in developing new therapeutic agents from natural products to inhibit mediators involved in the evolution of pain ( 31 ). Although some herbal extracts have been reported to alleviate pain in musculoskeletal disorders ( 18 , 19 ), to the best of our knowledge, this study is one of the first investigations conducted to investigate the effects of topical sesame oil on pain severity and frequency of received NSAIDs of patients with trauma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have shown a need for alternative and complementary therapy for pain management after trauma ( 18 , 19 ). Currently, therapeutic effects of some herbal products such as comfrey root (Symphytum officinale) extract are discussed in researches for short-term management of pain after ankle trauma ( 20 - 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…While Dr. Haltiwanger reports success in his practice with this TBI protocol, objective research is still needed in this area to substantiate his results. Table 1 16,18,[28][29][30][31][32][33][34] provides a summary of nutrition therapies that could be of benefit in TBI treatment.…”
Section: Nutrition Therapies For Tbimentioning
confidence: 99%